Сравнительный анализ российских и зарубежных образовательных программ по подготовке/переподготовке менеджеров сферы физической культуры и спорта - N. V. Kandaurova; I. V. Kulkova (Путеводитель предпринимателя)
Comparative analysis of Russian and foreign educational programs for training/retraining managers sphere of physical culture and sports In this paper, the problem of contradiction is updated when a power control system modernization of Russian sport, overdue real need for training / retraining managers of sports and sports organizations, able to quickly solve management problems encountered unforeseen, on the other hand, the absence of applied knowledge on economic subjects with a view to their implementation in practical management. The authors provide a theoretical analysis of domestic and foreign experience of educational training/ retraining managers of sports and sports organizations, on the basis of which the conclusions are advisory.